2019
DOI: 10.1007/s10067-019-04675-2
|View full text |Cite
|
Sign up to set email alerts
|

SAPHO: has the time come for tailored therapy?

Abstract: SAPHO (synovitis, acne, pustulosis, hyperostosis and osteitis) syndrome is a heterogeneous condition combining osteoarticular and cutaneous manifestations. Conventional treatments are mostly ineffective. We hereby report two patients, the first with an aggressive form of disease and the second with an incomplete response to two different anti-TNF-α agents. Both were successfully treated with tocilizumab and ustekinumab, respectively, over a long period of time. A narrative review of a biological therapy in SAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…The pathogenesis of SAPHO syndrome is still poorly understood because of its enigmatic etiology. 13 , 18 Numerous experimental studies have shown that the development and progression of this entity is induced by multifarious factors of which genetics, environmental effects, and bacterial or viral pathogens might be involved. 29 To date, two major hypotheses of the pathogenesis of SAPHO syndrome have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of SAPHO syndrome is still poorly understood because of its enigmatic etiology. 13 , 18 Numerous experimental studies have shown that the development and progression of this entity is induced by multifarious factors of which genetics, environmental effects, and bacterial or viral pathogens might be involved. 29 To date, two major hypotheses of the pathogenesis of SAPHO syndrome have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 11 Osseous lesions are mainly classified as necrosis, fibrosis, hyperostosis, and aberrant calcification, and these lesions always appear to be the combination of these findings. 12 , 13 The difficulty of diagnosis of this syndrome is increased in patients with only a single bone or skin symptom because symptomatic manifestations of two sites are not merged simultaneously. 10 , 14 , 15 Moreover, representative cutaneous symptoms with an average rate of 63.5% are ordinary.…”
Section: Introductionmentioning
confidence: 99%
“…Infliximab, etanercept, and adalimumab are the most commonly used TNF-α antagonists; however, patients with SAPHO who exhibit cutaneous manifestations do not respond well to these common therapies. 1 , 16 Recently developed cytokine-directed antibodies (e.g., anakinra, ustekinumab, secukinumab, and tocilizumab) have shown promising efficacy in some case reports and case series. 16 In addition, successful treatment of refractory SAPHO syndrome was achieved in one patient by using the JAK inhibitor tofacitinib 17 and in another patient by using apremilast (a specific phosphodiesterase-4 inhibitor); 18 those findings suggest the availability of further therapeutic options for the management of SAPHO syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome is a rare auto-inflammatory condition that shares musculoskeletal and cutaneous manifestations (113). Chronic recurrent multifocal osteomyelitis (CRMO) is considered the pediatric counterpart of SAPHO syndrome, arising from sterile osteomyelitis (Figures 10A-C).…”
Section: Sapho Syndrome and Crmomentioning
confidence: 99%